Conclusions of the digital health hub of the Transform Africa Summit (2018): strong government leadership and public-privatepartnerships are key prerequisites for sustainable scale up of digital health in Africa - Ngoc, Candide Tran; Bigirimana, Noella; Muneene, Derrick; Bataringaya, Juliet Evelyn; Barango, Prebo; Eskandar, Hani; Sina-Odunsi, Ayomide (BMC Proceedings, 2018)
The use of digital technologies to improve access to health is gaining momentum in Africa. This is more pertinent with the increasing penetration of mobile phone technology and internet use, and calls for innovative strategies to support implementation of the health-related Sustainable Development Goals and Universal Health Coverage on the continent. However, the huge potential benefits of digital health to advance health services delivery in Africa is yet to be fully harnessed due to critical challenges such as proliferation of pilot projects, poor coordination, inadequate preparedness of the African health workforce for digital health, lack of interoperability and inadequate sustainable financing, among others. To discuss these challenges and propose the way forward for rapid, cost-effective and sustainable deployment of digital health in Africa, a Digital Health Hub was held in Kigali from 8th to 9th May 2018 under the umbrella of the Transform Africa Summit 2018.
Keywords: Conference proceedings; Digital health; E-health; Digital health hub